STRATEGI GURU DALAM MEMPERKUAT KEPERCAYAAN DIRI ANAK USIA DINI DI TAMAN ANAK-ANAK - Salsabila; Mursid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyze teachers’ strategies for building self-confidence in early childhood students through active learning approaches at Al Azhar 29 Kindergarten in Semarang. The study employed a descriptive qualitative approach, with the research subjects consisting of one classroom teacher, one assistant teacher, and 24 children in the Al Wahhab Kindergarten B class. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the teacher implemented various strategies to develop children’s self-confidence, including morning pledge activities, providing opportunities to serve as class leaders during morning meetings, actively involving children in creating learning concept maps, presenting their work, offering positive reinforcement, engaging them in competitions, and assigning them as officials for the monthly ceremony. These various activities provide children with opportunities to perform, express their opinions, interact, and demonstrate their abilities. The barriers identified include differences in children’s personalities, an unsupportive family environment, and limited opportunities for individual guidance due to the relatively large class size. This study concludes that teacher strategies that are consistent, supportive, and centered on children’s active participation are effective in strengthening young children's self-confidence. The findings of this study imply that learning that provides ongoing opportunities to perform and a learning environment that values the child’s developmental process can serve as important tools in supporting the social-emotional development of young children.